Effect of Puumala hantavirus infection on human umbilical vein endothelial cell hemostatic function: platelet interactions, increased tissue factor expression and fibrinolysis regulator release - Goeijenbier, Marco; Meijers, Joost C. M.; Anfasa, Fatih; Roose, Jeroen M.; van de Weg, Cornelia A. M.; Bakhtiari, Kamran; Henttonen, Heikki; Vaheri, Antti; Osterhaus, Albert D. M. E.; van Gorp, Eric C. M.; Martina, Byron E. E. (Frontiers in Microbiology, 2015)
Puumala virus (PUUV) infection causes over 5000 cases of hemorrhagic fever in Europe annually and can influence the hemostatic balance extensively. Infection might lead to hemorrhage, while a recent study showed an increased risk of myocardial infarction during or shortly after PUUV infection. The mechanism by which this hantavirus influences the coagulation system remains unknown. Therefore we aimed to elucidate mechanisms explaining alterations seen in primary and secondary hemostasis during PUUV infection. By using low passage PUUV isolates to infect primary human umbilical vein endothelial cells (HUVECs) we were able to show alterations in the regulation of primary- and secondary hemostasis and in the release of fibrinolysis regulators. Our main finding was an activation of secondary hemostasis due to increased tissue factor expression leading to increased thrombin generation in a functional assay. Furthermore, we showed that during infection platelets adhered to HUVECs and subsequently specifically to PUUV virus particles. Infection of HUVECs with PUUV did not result in increased von Willebrand factor while they produced more plasminogen activator inhibitor type-1 (PAI-1) compared to controls. The PAI-1 produced in this model formed complexes with vitronectin. This is the first report that reveals a potential mechanism behind the pro-coagulant changes in PUUV patients, which could be the result of increased thrombin generation due to an increased tissue factor expression on endothelial cells during infection. Furthermore, we provide insight into the contribution of endothelial cell responses regarding hemostasis in PUUV pathogenesis.